DOI: 10.14264/uql.2018.607
|View full text |Cite
|
Sign up to set email alerts
|

The role of scaffolding in the instructional design of online, self-directed, inquiry-based learning environments: student engagement and learning approaches

Abstract: A. (2016). Development of scaffolded online modules to support self-regulated learning in chemistry concepts. In M. Schultz, S. Schmid, & T. Holme (Eds.), Technology and assessment strategies for improving student learning in chemistry (Vol. 1235, pp. 1-21). Washington, DC: American Chemical Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 406 publications
(541 reference statements)
0
7
0
Order By: Relevance
“…The details of data analysis coding technique have been reported in other studies in which four key constructs of behavioural engagement mentioned in Fig. 2 have been conceptualised (Al Mamun, 2018;. Al Mamun and Lawrie Smart Learning Environments (2023) 10:1…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The details of data analysis coding technique have been reported in other studies in which four key constructs of behavioural engagement mentioned in Fig. 2 have been conceptualised (Al Mamun, 2018;. Al Mamun and Lawrie Smart Learning Environments (2023) 10:1…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the predict, observe, explain, and evaluate (POEE) pedagogical design, an extended version of POE, has been utilised in this study to provide a series of inquiry phases for student learning in an asynchronous, self-directed, online environment. The details of the development of this pedagogical design have been reported elsewhere (Al Al Mamun and Lawrie Smart Learning Environments (2023) 10:1 Mamun, 2018;Al Mamun et al, 2020). Figure 3 shows the schematic representation of the POEE pedagogical framework.…”
Section: Instructional Methods Designmentioning
confidence: 99%
“…Fig. 2 The POEE scaffolding framework with scaffolding elements employed in the current study (Source: Al Mamun et al, 2020;Al Mamun, 2018) self-reported data, it was revealed that many students had prior learning experience with online simulations therefore may possess higher levels of self-efficacy, engagement, and performance than others (Al Al Mamun & Lawrie, 2023). We also anticipated that students who have higher ability levels will benefit more from the feedback and scaffolding provided by the simulation software and online learning platforms.…”
Section: Reflectionmentioning
confidence: 95%
“…Instructional scaffolding is an effective approach to support self-regulation during the LC interaction process (Al Mamun, 2018). The concept of scaffolding originated in the application of social constructivism as realized in the notion of the zone of proximal development (ZPD) (Vygotsky, 1978) and articulated specifically in the work of Wood et al (1976).…”
Section: Scaffolding Framework To Facilitate the Self-regulated Scien...mentioning
confidence: 99%
“…The POE scaffolding framework proposed by White and Gunstone (1992) is a popular scaffolding framework that can elicit students’ prior knowledge. It is considered as an effective instructional model to support students’ engagement in the inquiry process (Al Mamun, 2018).…”
Section: Scaffolding Framework To Facilitate the Self-regulated Scien...mentioning
confidence: 99%